2021
DOI: 10.1101/2021.07.16.21260629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring relationships between drought and epidemic cholera in Africa using generalised linear models

Abstract: Background: Temperature and precipitation are known to affect Vibrio cholerae outbreaks. Despite this, the impact of drought on outbreaks has been largely understudied. Africa is both drought and cholera prone and more research is needed in Africa to understand cholera dynamics in relation to drought. Methods: Here, we analyse a range of environmental and socioeconomic covariates and fit generalised linear models to publicly available national data, to test for associations with several indices of drought and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 39 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…These pre-existing vulnerabilities can be worsened in times of environmental and social extremes, which can act as a catalyst for outbreaks. Previous research has found several links between extreme events and cholera including floods, drought and conflict [18][19][20] , all of which have impacted Nigeria in recent decades. Risk factors leading to disease outbreaks include an inability to access routine care, fears over safety, disruption of WASH services and human displacement 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These pre-existing vulnerabilities can be worsened in times of environmental and social extremes, which can act as a catalyst for outbreaks. Previous research has found several links between extreme events and cholera including floods, drought and conflict [18][19][20] , all of which have impacted Nigeria in recent decades. Risk factors leading to disease outbreaks include an inability to access routine care, fears over safety, disruption of WASH services and human displacement 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on disaster-related infectious disease outbreaks have examined disasters in isolation 19,22 , while others do not include multiple pre-existing socio-economic factors into the methodology 26,27 . We aim to fill this research gap by evaluating the effects of multiple disaster types on cholera outbreaks, taking into context population vulnerability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found several environmental and socioeconomic links with cholera, including temperature, precipitation, poverty and water, sanitation, and hygiene (WASH) ( 3,4,5 ). Furthermore, extremes of these environmental and social conditions can act as catalysts for outbreaks, such as droughts, floods, and conflicts ( 6,7,8 ).…”
mentioning
confidence: 99%